Fundamentals and Applications of Focused Ultrasound-Assisted Cancer Immune Checkpoint Inhibition for Solid Tumors - Sepideh Jahangiri; François Yu (MDPI AG, 2024)
Despite spectacular clinical successes across several cancer types, immune checkpoint inhibition is effective only in subgroups of patients and suffers from significant systemic toxicities, highlighting the need to understand and locally overcome the mechanisms of therapeutic resistance. Similarly to other therapeutics, immunotherapies face delivery challenges (for example, antibodies need to reach their targets) and immunological barriers that are unique to solid tumors and their microenvironment. Interestingly, focused ultrasound (FUS), with or without microbubbles, which has been shown to enhance gene and drug delivery, notably in oncology, has been recently found to trigger immunological responses. In recent years, there has been a strong emphasis on understanding the biological and immunological effects of FUS for cancer therapy, and FUS is now emerging as an approach that can improve cancer immunotherapy. We herein review: (1) the immunological barriers implicated in ICI resistance; (2) the fundamentals of FUS +/− MB and the current knowledge on leveraging FUS +/− MB bioeffects for improving ICI therapy efficacy; (3) the immune profile of tumor models that have been successfully treated with FUS and ICI; and finally, (4) we discuss the challenges ahead for translating FUS and MB treatments to the clinic, highlighting the exciting perspectives for this new research area.